PERAN STRATEGI OPERASI DALAM MENCAPAI KEUNGGULAN KOMPETITIF BAGI PERUSAHAAN - Erni Widajanti (Universitas Slamet Riyadi, 2014)
In order to achieve a competitive advantage, companies should always attention and adjust to the changing corporate environment. Changes in corporate environments including internal environment (egg, changes in size, structure) and external environment (egg: change desires and expectations of consumers, changes in technology, companies, competitors). Adjustments to the environment can have an impact on a change in operating strategy. Basically to achieve competitive advantage through the establishment and implementation of operating strategies can be done through: leadership in product differentiation, cost leadership and leadership in response to the speed of the response. Keywords: Competitive advantage, operation strategy.